Direct Measurement of Nuclear Dependence of Charged Current Quasielasticlike Neutrino Interactions Using MINERvA - Betancourt M. (2017)
Charged-current νμ interactions on carbon, iron, and lead with a final state hadronic system of one or more protons with zero mesons are used to investigate the influence of the nuclear environment on quasielasticlike interactions. The transferred four-momentum squared to the target nucleus, Q2, is reconstructed based on the kinematics of the leading proton, and differential cross sections versus Q2 and the cross-section ratios of iron, lead, and carbon to scintillator are measured for the first time in a single experiment. The measurements show a dependence on the atomic number. While the quasielasticlike scattering on carbon is compatible with predictions, the trends exhibited by scattering on iron and lead favor a prediction with intranuclear rescattering of hadrons accounted for by a conventional particle cascade treatment. These measurements help discriminate between different models of both initial state nucleons and final state interactions used in the neutrino oscillation experiments.